Swedish (L1) and English (L2) Argumentative Writing of Upper Secondary Students with Reading Difficulties - Sehlström, Pär; Waldmann, Christian; Steinvall, Anders; Levlin, Maria (L1-Educational Studies in Language and Literature, 2022)
Writing has been identified as a challenge for students with reading difficulties. This study contributes to previous research by exploring argumentative writing in L1 (Swedish) and L2 (English) in a group of students with reading difficulties in upper secondary school. Participants were 19 students with typical reading, 19 students with poor decoding, and 9 students with poor comprehension. A majority of students attended vocational programmes. Written text quality was assessed by using an adapted version of Jacobs et al.’s (1981) analytic scoring scheme including content, organisation, cohesion, vocabulary, language use, spelling, and punctuation. Students with reading difficulties (regardless of reader subgroup) were found to perform poorly in all categories in both L1 and L2, with spelling being particularly challenging in L1, and cohesion, language use, spelling, and punctuation in L2. Significant differences were found between students with poor comprehension and students with typical reading in cohesion, language use and spelling in L2. Few other significant differences were identified possibly due to an overall poor writing outcome also for students with typical reading. This general poor outcome in writing is discussed in relation to previous studies on writing among students with reading difficulties and writing in vocational programmes.